The epithelial-mesenchymal transition regulators Twist, Slug, and Snail are associated with aggressive tumour features and poor outcome in prostate cancer patients - Astrid Børretzen; Karsten Gravdal; Svein A Haukaas; Monica Mannelqvist; Christian Beisland; Lars A Akslen; Ole J Halvorsen (Wiley, 2021)
Abstract The prognostic importance of transcription factors promoting epithelial-mesenchymal transition (EMT) and angiogenesis has not been well explored in prostate cancer patients with long follow‐up, nor the interplay between these factors. The objective of this study was to assess the individual protein expression and co‐expression of Twist, Slug (Snai2), Snail (Snai1), and hypoxia‐inducible factor‐1 alpha (Hif‐1α) in prostate cancer in relation to EMT, angiogenesis, hypoxia, tumour features, disease recurrence, and patient survival. Immunohistochemical staining was performed on tissue microarray sections from 338 radical prostatectomies with long follow‐up. In addition, 41 cases of prostatic hyperplasia, 33 non‐skeletal metastases, 13 skeletal metastases, and 33 castration‐resistant prostate carcinomas were included. Our findings were validated in external gene expression data sets. Twist was overexpressed in primary prostate cancer and markedly reduced in distant metastases (p < 0.0005). Strong expression of Twist and Slug was associated with Hif‐1α in localised prostate cancer (p ≤ 0.001), and strong Twist was associated with Hif‐1α in castration‐resistant carcinomas (p = 0.044). Twist, Slug, and increased Snail at the tumour stromal border were associated with vascular factors (p ≤ 0.045). Each of the three EMT‐regulating transcription factors were associated with aggressive tumour features and shorter time to recurrence and cancer‐specific death. Notably, the co‐expression of factors demonstrated an enhanced influence on outcome. In the subgroup of E‐cadherinlow carcinomas, strong Slug was associated with shorter time to all end points and was an independent predictor of time to multiple end points, including cancer‐specific death (hazard ratio 3.0, p = 0.041). To conclude, we demonstrate an important relation between EMT, hypoxia, and angiogenesis and a strong link between the investigated EMT regulators and aggressive tumour features and poor patient outcome in prostate cancer. Despite the retrospective nature of this long‐term study, our findings could have a significant impact on the future treatment of prostate cancer, where tailored therapies might be directed simultaneously against epithelial-mesenchymal phenotypes, angiogenesis, and tumour hypoxia.